Giant omphalocele closure utilizing botulinum toxin - Jessica L. Rauh; Leah M. Sieren (Journal of Pediatric Surgery Case Reports, 2020)
An omphalocele is a rare congenital abdominal wall defect of the umbilical ring. A giant omphalocele is typically defined as 5 cm or larger. Here we present a case of utilizing botulinum toxin to aid in closure of a giant omphalocele. Lack of abdominal domain prevented visceral reduction and initial treatment involved and alloderm silo and wound vac dressing allowing granulation tissue epithelialization. Patient underwent two rounds of botox injections and fascial closure was obtained. Chemical component separation with botox injection of the abdominal wall musculature is safe and effective for augmenting closure of giant omphalocele.